Assessment of sustainable drainage strategies in urban water systems using urban water metabolism and multi-criteria decision analyses - da Silva Garcia, Maria Vitória [UNESP]; Moruzzi, Rodrigo Braga [UNESP]; Behzadian, Kourosh (My University, 2023)
The simulation of urban water metabolism (UWM) allows for the tracking of all water, energy, and material flows within urban water systems (UWSs) and the quantification of their performance, including emissions into the air, water, and soil. This study evaluates seven drainage strategies (DSs) within conventional and sustainable urban drainage systems (SUDSs) using UWM and multicriteria decision analysis (MCDA). The DSs were designed to assess their corresponding UWM performances, employing key performance indicators (KPIs) related to sewer system balance, energy consumption, greenhouse gas (GHG) emissions, acidification, eutrophication, contamination, and sludge production. The outcomes were ranked using the compromise programming MCDA model. The top three strategies were permeable pavements, green spaces, and infiltration trenches and sand filters. The approach used for the evaluation of DS can provide valuable insights for decision-makers, support the promotion of sustainable integrated UWS management and adaptation, and accommodate design variations in urban drainage. Sensitivity analysis on uncertain parameters and KPI selection also contributed to robust and sustainable urban drainage solutions.
Keywords: decision-making; metabolic system; performance; SUDS; urban drainage; WaterMet2